Combination of Aerobic Exercise and Continuous Environmental Enrichment Improves Adult Male Rats’ Spatial Memory: Study on Hippocampal Insulin Like Growth Factor 1 (IGF-1) and Fibroblast Growth Factor 2 (FGF-2) Expression - Sophie Yolanda; Sri Redjeki; Trinovita Andraini; Dewi Irawati Soeria Santoso; Nurhadi Ibrahim; Rena Mailani (The Prodia Education and Research Institute (PERI), 2019)
BACKGROUND: Memory declines with the progression of age through the neurodegeneration process. Aerobic exercise and environmental enrichment can delay neurodegeneration by improving neuroplasticity via expression of insulin like growth factor 1 (IGF-1), fibroblast growth factor 2 (FGF-2) and other proteins. Combination treatment of aerobic exercise and continuous environmental enrichment and their effect on the expression of IGF-1 and FGF-2 which were expected to improve memory function has not been studied previously. Thus, this study aimed to observe it.METHODS: This is an experimental research using 24 male Wistar rats (Rattus norvegicus, 300-400 g, age 7-8 months) divided randomly into 4 groups: control (C), aerobic exercise (A), continuous (EE), and combination of aerobic exercise and continuous environmental enrichment (A-EE). At the end of an 8-week treatment, rats were sacrificed, and an enzyme-linked immunosorbent assay (ELISA) examination was performed to assess hippocampal IGF-1 and FGF-2 levels.RESULTS: In the 8th week, A-EE group showed the best improvement in rats’ spatial memory (47.84±10.6 %) followed by EE group (45.03±4.1 %), A group (38.61±3.8 %), and C group (22.76±7.12 %). However, A-EE group’s hippocampal IGF-1 (16.21±7.56 ng/mg protein) and FGF-2 (1.29±0.57 ng/mg protein) expression were not higher than other groups.CONCLUSION: Improvement in memory function in the combination group is a result of induction of various growth factors’ expression in the hippocampus, including IGF-1 and FGF-2, but the primary pathway of memory function improvement may be from other growth factors.KEYWORDS: spatial memory, aerobic exercise, environmental enrichment, hippocampus, IGF-1, FGF-2